Dainos by Martin Ludwig Rhesa and other Lithuanian Heritage in Moscow - Rekašiūtė, Kotryna (Knygotyra, 2022)
The State Public Historical Library of Russia is storing some significant 18th and 19th century Lithuanian publications related with Prussian Lithuania. They include a copy of the first edition (1825) of the first collection of Lithuanian folk songs Dainos oder Litthauische Volkslieder (en. Dainos [lt. Songs] or Lithuanian Folk Songs) by Martin Ludwig Rhesa (1776–1840) which used to belong to one of reviewers of this publication. On the grounds of the provenience inscriptions, the article is striving to establish the former owners of the copy of the first ever Lithuanian collection of songs and to discuss some of the Lithuanian culture publications related with Prussian Lithuania stored at the Russian Historical Library. The full list of the Lituanistics related publications and their library classification sygnatures are presented in the Annex to this article.
Keywords: Fr. Höpker; Ernst Friedrich Mooyer; Moscow; State Public Historical Library of Russia; Lituanistics; Prussian Lithuania; Martin Ludwig Rhesa; Dainos (Songs); rare publications